A GO/CoMo3S13 chalcogel heterostructure with rich catalytic Mo–S–Co bridge sites for the hydrogen evolution reaction. Issue 26 (14th June 2022) - Ha, Thanh Duy Cam; Do, Ha Huu; Lee, Heehyeon; Ha, Nguyen Ngoc; Ha, Nguyen Thi Thu; Ahn, Sang Hyun; Oh, Youngtak; Kim, Soo Young; Kim, Myung-Gil
Abstract : This article proposes an efficient GO/CoMo3 S13 chalcogel heterostructure catalyst for the hydrogen evolution reaction through the synergetic combination of the active Mo–S–Co bridge sites with shortened charge transport on graphene oxide. Abstract : Molybdenum disulfide (MoS2 )-based materials are extensively studied as promising hydrogen evolution reaction (HER) catalysts. In order to bring out the full potential of chalcogenide chemistry, precise control over the active sulfur sites and enhancement of electronic conductivity need to be achieved. This study develops a highly active HER catalyst with an optimized active site-controlled cobalt molybdenum sulfide (CoMo3 S13 ) chalcogel/graphene oxide aerogel heterostructure. The highly active CoMo3 S13 chalcogel catalyst was achieved by the synergetic catalytic sites of [Mo3 S13 ] 2− and the Mo–S–Co bridge. The optimized GO/CoMo3 S13 chalcogel heterostructure catalyst exhibited high catalytic HER performance with an overvoltage of 130 mV, a current density of 10 mA cm −2, a small Tafel slope of 40.1 mV dec −1, and remarkable stability after 12 h of testing. This study presents a successful example of a synergistic heterostructure exploiting both the appealing electrical functionality of GO and catalytically active [Mo3 S13 ] 2− sites.